The Concept of “Unusual Punishments” in Anglo-American Law: The Death Penalty as Arbitrary, Discriminatory, and Cruel and Unusual - Bessler, John D. (2018)
The Eighth Amendment of the U.S. Constitution, like the English Bill of Rights before it, safeguards against the infliction of “cruel and unusual punishments.” To better understand the meaning of that provision, this Article explores the concept of “unusual punishments” and its opposite, “usual punishments.” In particular, this Article traces the use of the “usual” and “unusual” punishments terminology in Anglo-American sources to shed new light on the Eighth Amendment’s Cruel and Unusual Punishments Clause. The Article surveys historical references to “usual” and “unusual” punishments in early English and American texts, then analyzes the development of American constitutional law as it relates to the dividing line between “usual” and “unusual” punishments. The Article concludes that customary punishments were often described as “usual punishments,” but that it was understood—and has long been understood by the U.S. Supreme Court itself—that punishments might become “unusual” over time. The Article further concludes that the protection against the infliction of “cruel and unusual punishments” arose out of a desire to protect against torture and the arbitrary infliction of punishments, including ones that were either out of step with societal values or that had become at odds with societal norms. In light of the decline in death sentences and executions, the Fourteenth Amendment’s post-Civil War guarantee of “due process” and “equal protection of the laws,” and the Eighth Amendment’s long-standing prohibition against torture, this Article concludes that America’s death penalty, which has always been cruel, has now become a highly arbitrary and unusual punishment. The Article concludes that life sentences are now the “usual” punishment for the most serious crimes, and that the death penalty is now “unusual” and that its use is incompatible with the text and guarantees of the U.S. Constitution. Not only are executions now extremely rare, especially in comparison to life sentences, but the death penalty is administered in an arbitrary, error-prone, discriminatory, and torturous manner